Changes in the Management of Patients having Radical Radiotherapy for Lung Cancer during the First Wave of the COVID-19 Pandemic in the UK. Issue 1 (January 2022) - Banfill, K.; Croxford, W.; Fornacon-Wood, I.; Wicks, K.; Ahmad, S.; Britten, A.; Carson, C.; Dorey, N.; Hatton, M.; Hiley, C.; Thippu Jayaprakash, K.; Jegannathen, A.; et al.
Abstract: Aims: In response to the COVID-19 pandemic, guidelines on reduced fractionation for patients treated with curative-intent radiotherapy were published, aimed at reducing the number of hospital attendances and potential exposure of vulnerable patients to minimise the risk of COVID-19 infection. We describe the changes that took place in the management of patients with stage I–III lung cancer from April to October 2020. Materials and methods: Lung Radiotherapy during the COVID-19 Pandemic (COVID-RT Lung) is a prospective multicentre UK cohort study. The inclusion criteria were: patients with stage I–III lung cancer referred for and/or treated with radical radiotherapy between 2nd April and 2nd October 2020. Patients who had had a change in their management and those who continued with standard management were included. Data on demographics, COVID-19 diagnosis, diagnostic work-up, radiotherapy and systemic treatment were collected and reported as counts and percentages. Patient characteristics associated with a change in treatment were analysed using multivariable binary logistic regression. Results: In total, 1553 patients were included (median age 72 years, 49% female); 93 (12%) had a change to their diagnostic investigation and 528 (34%) had a change to their treatment from their centre's standard of care as a result of the COVID-19 pandemic. Age ≥70 years, male gender and stage III disease were associated with a change in treatment on multivariable analysis. Patients who had their treatment changed had a median of 15 fractions of radiotherapy compared with a median of 20 fractions in those who did not have their treatment changed. Low rates of COVID-19 infection were seen during or after radiotherapy, with only 21 patients (1.4%) developing the disease. Conclusions: The COVID-19 pandemic resulted in changes to patient treatment in line with national recommendations. The main change was an increase in hypofractionation. Further work is ongoing to analyse the impact of these changes on patient outcomes. Highlights: The first wave of the COVID-19 pandemic led to changes in the management of patients with stage I–III lung cancer. Diagnostic investigations were altered in 12% of patients referred for radical radiotherapy. A third of patients had a change to standard of care treatment. Men, patients aged ≥70 years or those with stage III lung cancer were more likely to have their treatment changed. 2.1% of patients had a diagnosis of COVID-19 before, during or after radiotherapy.